THE USE OF “WORD-PROCESSING” TO IMPROVE THE WRITING SKILL OF THE 11TH GRADERS (RETAIN, 2016)
THE USE OF “WORD-PROCESSING” TO IMPROVE THE WRITING SKILL OF THE 11TH GRADERS Onky Muhammad English Education, English Department, Faculty of Languages and Arts, State University of Surabaya onkymuhammad@mhs.unesa.ac.id Dra. Theresia Kumalarini, M.Pd. English Department, Faculty of Languages and Arts, State University of Surabaya Theresiakumalarini@unesa.ac.id Abstract Being able to write in the target language is considered one of the successful language learner indicators because writing is a complex productive language skill. It plays a great role in the process of learning new languages. Computer Assisted Language Learning relies on any computer program to assist the language learners learn their new languages. Word-processing as one of the CALL programs provides various features that could assist learners compose a written text. This research takes 15 eleventh graders to be assigned to both pre and post-test since this research has a one group pre-test post-test design. The treatment is conducted in 5 consecutive meetings alongside with a project based learning being implemented. Then, the post-test is given to check the output of the treatment. The difference in writing components appears significant implying that the word-processing truly assists learners compose an analytical exposition text. Hence, it is now statistically proven that the eleventh graders could compose analytical exposition text although in the curriculum the basic competence of the related text is only limited into reading and listening. Keywords: CALL, computer, word-processing, Microsoft word, writing, analytical expostition Abstrak Kemampuan menulis ini menjadi salah satu indikator pembelajaran Bahasa yang berhasil karena Menulis adalah sebuah kemampuan produktif Bahasa yang rumit. kemampuan menulis ini memainkan perannya yang sangat besar terhadap pembelajaran Bahasa baru. Computer Assisted Language Learning adalah teknik mengajar yang mengandalkan program komputer untuk membantu para pembelajar Bahasa mempelajari Bahasa yang diinginkannya. Word-processing yang mana adalah salah satu dari program yang termasuk dalam CALL menyediakan fitur-fitur yang beraneka ragam sehingga dapat membantu dalam hal penyusunan sebuah teks tulis. Penelitian ini mengambil 15 siswa kelas 11 yang selanjutnya akan diberikan pre-test dan post-test karena sesuai dengan desain penelitian yang mana adalah ‘one group pre-test post-test design’. Pemberian perlakuan diadakan selama 5 pertemuan beruntun dengan menggunakan model pembelajaran Project Based Learning. Lalu, post-test diberikan untuk melihat hasil dari perlakuan tersebut. Perbedaan yang nampak pada komponen tulisan para siswa cukup signifikan yang juga mengisyaratkan bahwa program word-processing sangat membantu penyusunan teks analytical exposition. Oleh karena itu, sekarang telah terbukti secara ilmiah bahwasanya siswa kelas 11 mampu membuat dan menyusun teks analytical exposition meskipun Kompetensi Dasar yang disediakan dalam Kurikulum membatasi kegiatan pembelajaran yang berhubungan dengan teks tersebut hanya dalam lingkup kemampuan reading dan listening. Kata Kunci: CALL, komputer, word-processing, Microsoft word, menulis, analytical expostition